A Social Psychological Exploration of Tenure Reform in a Cape Town Housing Project - Brusser, Paul (Department of Psychology, 2022)
Research into tenure reform in South Africa, in the form of allocating private property rights in the form of title deeds, has yielded unclear results in terms of economic upliftment of communities. There is a lack of qualitative information about how communities engage with land titling projects, with existing research being largely survey based. This research involved semi-structured interviews with a sample of twelve participants from a land titling project in Vukuzenzele, Cape Town, with the aim of understanding their decision-making process around whether to get their title deeds. Interviews were subjected to a thematic analysis, out of which nine themes emerged: Trust, Security of Ownership, Tyranny and Authority, Money and Cost, Community Mentality and Support, Capacity for Agency, Forms and Norms, Struggle, and Self-Ownership. While land titling has been justified in neoliberal economic terms, this research showed that capital gains were not the primary motivation of participants. The material and psychosocial possibility of security of ownership emerged as a primary motivation. In order to attain that security, the community had to navigate new areas of knowledge and norms, renegotiating social representations of trust and authority. This research could assist stakeholders in understanding how to approach communities and by what metrics the outcome of titling projects could be assessed.